Handel zagraniczny w teorii wolnego handlu i protekcjonizmu po drugiej wojnie światowej - Domiter, Małgorzata (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
The issue of liberalism and protectionism in foreign trade has always been in centre of attention of theorists and practitioners. On the basis of the conducted analysis of export and import, in view of the protectionism and free trade theory, it has been proven that both liberalism and protectionism, in their pure forms, hardly ever occur in contemporary world. Certain tendencies to liberalism and trading protectionism operate instead, contingent upon the economical situation of a particular country The phenomenon of selective protectionism towards some selected "sensitive" production branches is said to have been functioning nowadays. It is called neoprotectionism. However, the attitude of liberalism may be applied on an appropriate level of economic development in a given country. Yet, it is not always favourable for the developing countries. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (16); 2008; nr 1193, s. 56-72